The 2012 U.S. Presidential race : impact on US policy on China and Southeast Asia - Freise, Christopher (2012)
Mitt Romney, the presumptive Republican nominee for president, has been highly critical of President Obama’s foreign policy. What impact, if any, would a Romney presidency have upon American foreign policy towards Southeast Asia and China?